Biotechnology and Intellectual Property Rights: Legal and Social Implications - Singh, Kshitij Kumar (Springer, 2015)
This book offers a valuable contribution to contemporary legal literature, providing deep insights into the interface between law and genetics, highlighting emerging issues and providing meaningful solutions to current problems. It will be of interest to a broad readership, including academics, lawyers, policy makers and scholars engaged in interdisciplinary research.